Adsorption of Rhodamine 6G and humic acids on composite bentonite–alginate in single and binary systems - Fatima Gomri; Gisèle Finqueneisel; Thierry Zimny; Sophia A. Korili; Antonio Gil; Mokhtar Boutahala (Applied Water Science, 2018)
Abstract In this work, the preparation, characterization, and sorption of rhodamine 6G and humic acids on a composite sodium alginate–bentonite were investigated. Their structure and morphology were analyzed by several techniques, including Fourier transform infrared spectroscopy, X-ray diffraction, and N2 adsorption at − 196 °C. A synergetic sorption mechanism was observed in binary systems; humic acids adsorption was enhanced by the presence of Rh6G in the mixture. The kinetic studies revealed that the sorption follows a pseudo-first-order kinetic model and the sorption capacities of Rh6G increased with the pH value. The Langmuir isothermal model well described the adsorption isotherm data, showing a maximum adsorption capacity for Rh6G up to 429.5 mg/g at 20 °C. On the basis of the data of the present investigation, it is possible to conclude that the composite exhibited excellent affinity for the dye and humic acids, and it can be applied to treat wastewater containing dye and natural organic matter.